PENGARUH STORE ATMOSPHERE, KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA DISTRO HORNY CUPCAKES SEMARANG - Putri Septiana Dewi, 13.05.51.0050 (Students Journal of Economic and Management, 2017)
This purpose of this study was to analysis the effect of store atmosphere, product quality, perceived price, and brand image to buying decision of Distro Horny Cupcakes Semarang. The population in this study is customers Distro Horny Cupcakes with criterian have made purchase of the product Horny Cupcakes. The number of samples studied were as many as 108 people were selected as respondents used purposive sampling technique. Data collection methods used in this study was questionnaire filled out by respondents. The analysis technique has been done by using validity test, reliability test, classic assumption test,multiple linear regressions test, model feasibility test and hypothesis significance test.Data processing using SPSS Version 19th. The results of this study showed that store atmosphere, product quality,perceived price, and brand image have positive effect and significant on buying decision. Keyword: Store Atmosphere, Product Quality, Perceived Price, Brand Image and Buying Decision